Application of virtual reality simulation in firefighter training for the development of decision-making competences - Reis, Vitor (2020)
This paper focuses on the training of firefighters, using simulated scenarios in virtual reality, to develop decision-making competences in the management of relief operations. Through the action research method, a training program was designed and improved to develop the competences considered critical in the field of decision making in the context of fire brigade interventions, using simulation exercises with scenarios in virtual reality. During two action research cycles, a pilot training course was conducted for a group of eight internal and external trainers from the Portuguese National Fire Service School, and a second course for eight fire officers from different Firefighters' corps. The data collected and the comparative analysis on the performance of the two groups of trainees, as well as the trainers' and trainees' perception in terms of evaluation of the training course, allowed to identify corrections and introduce changes, in the logic of continuous improvement of the training product. The results achieved in the research work demonstrated the adequacy of the training program and the use of virtual reality simulation, distinguishing a set of orientations that can be considered in similar formative contexts.